Giannozzo Manetti the life of a Florentine humanist - Marsh, David 1950- (Harvard University Press, 2019)
A celebrated orator, historian, philosopher, and statesman, Giannozzo Manetti (1396-1459) was one of the most remarkable figures of the Italian Renaissance. As contemporaries noted, his intellectual versatility--including an interest in architecture--linked him to Leon Battista Alberti, the renowned "universal man" of the Renaissance. Like Alberti, Manetti wrote in both Latin and Italian, and made new translations of canonical texts such as Aristotle, thus replacing the faulty medieval renderings that were the mainstay of Scholastic thought. A pious Christian, he translated the New Testament from Greek into Latin, thus challenging the centuries-old Vulgate; and he was the first scholar since Jerome to translate the Psalms from the original Hebrew. To forestall possible critics, he penned a treatise expounding his philological methods in translating scripture. Delivered over the course of nearly twenty years, his addresses to magistrates, commanders, princes, and popes furnish a vivid picture of Quattrocento politics and diplomacy. This authoritative biography, the first in any modern language, both describes chronologically the events of his extraordinary career, and analyzes his numerous and wide-ranging writings, which confirm Manetti's status as an exemplar of the spirit of the Italian Renaissance.--
1910
Keywords: Manettus, Iannotius -- 1396-1459; Manetti, Giannozzo / 1396-1459; Humanists / Italy / Biography; Humanists; Italy; Biography; Biografie